The fate of cadmium during ferrihydrite phase transformation affected by dissolved organic matter: Insights from organic-mineral interaction - Pan, Xiaofan; Huang, Xin; Deng, Ning (Chemical geology, 2024)
Ferrihydrite (Fh) is an important scavenger for sequestering cadmium (Cd). However, Fh is poorly crystallized and tends to undergo phase transformation under the impact of dissolved organic matter (DOM). The roles of DOM in Fh transformation pathway and the consequent Cd2+ remobilization behavior remain debate due to its structural heterogeneity and diversity. Herein, formic acid (FA), oxalic acid (Ox), and citric acid (CA) were selected as model DOM, which have one, two, and three carboxyl ligands, respectively. Fe K-edge extended X-ray absorption fine structure (EXAFS) spectra revealed an organic-specific correlation between Fh transformation and Cd2+ transport. FA with monodentate carboxyl ligand, lacking binding with Fh particles, had negligible influence on transformation dynamics and Cd2+ transport. The complexation of bidentate Ox with Fh particles impaired the stability of Fe(O,OH)6 octahedra, accelerating Fh phase transformation, thereby increasing Cd2+ release. During the subsequent recrystallization, Ox guided crystal growth via oriented attachment, which possibly occluded the remaining Cd2+ within structural defects of the secondary minerals. Conversely, tridentate CA exhibited a strong affinity with Fh, resulting in the formation of ferric citrate surface complexes that stabilized Fh against transformation and thus enhanced the long-term immobilization of Cd2+. These findings highlight the significant role of organic-ion/mineral interactions in Fh transformation, which are fundamentally linked to predicting Cd2+ transport behavior in environmental systems. [Display omitted]